Noncovalent Approach toward the Construction of Nanofluidic Diodes with pH-Reversible Rectifying Properties: Insights from Theory and Experiment - Perez Mitta, Gonzalo (2017)
In this paper, the fabrication of a biomimetic nanofluidic diode whose ionic transport characteristics can be completely modulated with the proton concentration in solution is demonstrated. The fabrication procedure involves the electrostatic assembly of poly(allylamine hydrochloride) (PAH) into a track-etched conical nanochannel. A fully reversible, zwitterionic-like behavior with important implications for the supramolecular interactions of the PAH within confined spaces was observed. The experimental design constitutes a facile venue for the fabrication of functional nanofluidic devices and paves the way for a number of applications in nanofluidics and biosensing. Furthermore, in order to explain the experimental results and to obtain physicochemical information about the system, theoretical modeling using a continuous model based on Poisson-Nernst-Planck equations and a stochastic model using Monte Carlo simulations were performed. Good agreement between experiments and theory was found.